COMMUNICATIVE COMPETENCIES AMONG BIOLOGY TEACHERS AND THEIR RELATIONSHIP TO CLASS INTERACTION - Mayadah Abdulsattar Abbas (Scholars Digest Publishing, 2025)
The aim of the research is to: 1- Build a scale that measures the levels of communication competencies among biology teachers.
Keywords: communicative competencies, biology teachers, classroom interaction.